2014
DOI: 10.13065/jksdh.2014.14.05.667
|View full text |Cite
|
Sign up to set email alerts
|

Problem-solving ability of dental hygiene students in accordance by meta-cognition level

Abstract: Objectives : The purpose of this study was to examine classifying the level and accuracy of the meta-cognitive level of students and dental hygiene, and to understand the impact on the process of problem solving and accordingly, it is intended to provide a basis for learning strategies.Methods : A self-reported questionnaire was filled out by 328 dental hygiene students in 3 colleges in Gyeonggi-do and Chungnam. Data were analyzed by the frequency analysis, one-way ANOVA, Scheffe's post-hoc test, Pearson's cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…Similarly, Jeoun's study 30) also found that learning flow, metacognition, and subjective grades were factors affecting problem-solving abilities, which is consistent with the results of this study. On the other hand, Jun et al's study 28) reported no correlation between metacognition levels and problem-solving abilities among dental hygiene college students, which differs from the findings of this study. These discrepancies might be attributed to differences in the study populations, methods, or other variables, and they highlight the complexity of understanding the relationships between metacognition, learning flow, and problem-solving abilities.…”
Section: Key Results and Comparisoncontrasting
confidence: 99%
See 2 more Smart Citations
“…Similarly, Jeoun's study 30) also found that learning flow, metacognition, and subjective grades were factors affecting problem-solving abilities, which is consistent with the results of this study. On the other hand, Jun et al's study 28) reported no correlation between metacognition levels and problem-solving abilities among dental hygiene college students, which differs from the findings of this study. These discrepancies might be attributed to differences in the study populations, methods, or other variables, and they highlight the complexity of understanding the relationships between metacognition, learning flow, and problem-solving abilities.…”
Section: Key Results and Comparisoncontrasting
confidence: 99%
“…Once again, the scores of dental hygiene students in this study seem to be lower. Furthermore, in a study involving dental hygiene students from the first to the third year, metacognition was at 4.43±0.76 on a 7-point scale, and problem-solving ability was at 2.82±0.54 on a 5-point scale 28) . When compared to these results, it is evident that the participants in this study had lower average scores.…”
Section: Key Results and Comparisonmentioning
confidence: 99%
See 1 more Smart Citation